Prediction of Bankruptcy of Indonesian Sharia Banking After The COVID-19 Pandemic - Latif, Abdul (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to measure the resilience of Indonesia's Islamic banking industry to the risk of bankruptcy after the COVID-19 pandemic. In this study, the CAR ratio is used which describes the level of capital adequacy of Islamic banking as the main variable. The regression variable is the probability of bankruptcy between 1 and 0 using changes in capital buffering. Economic Growth Rate, Bank Indonesia Certificate Interest Rate, and Inflation Rate as regressor variables. To anticipate the existence of endogenous variables, the Rupiah Exchange Rate, The Federal Reserve Interest Rate, and Money Supply (M2) are used as control variables. Data obtained from statistics from Bank Indonesia and the Financial Services Authority in the research period May 2015 to December 2022 Data analysis in predicting the probability of bankruptcy used the Probit Logit method with robust error standards. At a significance of = 5%, Probit's regression results show that significant economic growth (GDP) has a positive effect, while the Federal Reserve's interest rate hurts the probability of bankruptcy, which generally means a decrease in bankruptcy risk due to increased capital buffering and resistance of the Islamic banking industry during the Covid 19 pandemic. With Robust Standard Error, this model predicts precisely with a Count R2 value of 89.66%, a sensitivity value of 87.50%, and a specificity value of 91.18%.